Visualizing and Manipulating Focal Adhesion Kinase Regulation in Live Cells - Ritt, Michael (American Society for Biochemistry and Molecular Biology, 2013)
Focal Adhesion Kinase (FAK) is essential for cell migration and plays an important role in tumor metastasis. However, the complex intermolecular and intramolecular interactions that regulate FAK activity at the focal adhesion remain unresolved. We have engineered a toolbox of FRET sensors that retain all of the individual FAK domains but modulate a key intramolecular regulatory interaction between the band 4.1/ezrin/radixin/moesin (FERM) and kinase domains of FAK. We demonstrate systematic control and quantitative measurement of the FERM-kinase interaction at focal adhesions, which in turn allows us to control cell migration. Using these sensors, we find that Tyr-397 phosphorylation, rather than kinase activity of FAK, is the key determinant of cell migration. Our sensors directly demonstrate, for the first time, a pH-dependent change in a protein-protein interaction at a macromolecular structure in live cells. The FERM-kinase interaction at focal adhesions is enhanced at acidic pH, with a concomitant decrease in Tyr-397 phosphorylation, providing a potential mechanism for enhanced migration of cancer cells.